3-total edge product cordial labeling of wheel related graphs (MATEMATIKA, 2017)
For a graph G = (V (G), E(G)), an edge labeling function f : E(G) → {0, 1, · · · , k − 1} where k is an integer, 2 ≤ k ≤ |E(G)|, induces a vertex labeling function f*: V (G) → {0, 1, · · · , k − 1} such that f*(v) is the product of the labels of the edges incident to v (mod k). This function f is called k-total edge product cordial (or simply k-TEPC) labeling of G if |(vf (i) + ef (i)) − (vf (j) + ef (j))| ≤ 1 for all i, j ϵ {0, 1, · · · , k−1}. In this paper, 3-total edge product cordial labeling for wheel related graphs is determined.